Integrating Technological and Educational Collaborations: Enhancing Leadership and Participation in STEM Fields - Toolo, Lineo (Universitas Terbuka, 2023)
This study investigates the advancement of underrepresented groups in leadership roles within the fields of Science, Technology, Engineering, and Mathematics (STEM), areas traditionally dominated by their male counterparts. Through a convergent sequential mixed method, data was collected using 105 questionnaires and six semi-structured interviews involving students, lecturers, government officials, and university admissions administrators in the STEM disciplines. A concurrent triangulation strategy was applied for simultaneous quantitative and qualitative data analysis, utilizing MS Excel for the numerical data and thematic analysis for the narrative information. The research also examined statistical documents to assess the enrollment disparity among underrepresented groups and the presence of specific development programs in universities aimed at addressing this imbalance. Findings suggest that targeted and culturally informed collaborative efforts can effectively encourage the ascent of underrepresented demographics into STEM leadership roles in South African universities. The implications of the study are broad, given that the research spanned two distinct universities, implying that the strategies identified could inform actions across different educational institutions to foster inclusivity and equality in STEM leadership.